Integrated Digital Counseling: Inovasi Layanan BK Berbasis Teknologi di Sekolah - Kesia Simanjuntak; Rivanti Br. Sinuraya; Arlia Ananta Salsabila; Elza Tiurmaida Rimmauli Silalahi (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to design an integrated digital counseling service that can be implemented in SMA Negeri 17 Medan. Guidance and Counseling (BK) services in schools often face obstacles such as students' reluctance to directly visit the BK room, limited access outside school hours, and students' difficulty in expressing feelings in face-to-face settings. Through needs analysis, five main problems were identified: shame/fear in direct consultation, limited access time, difficulty expressing feelings, low utilization of BK services, and suboptimal early detection of student problems. This service design uses multiple digital platforms, including WhatsApp for counseling chat, Google Form for digital assessment and evaluation, Google Meet for online counseling sessions, and Instagram for information dissemination. The service flow includes: student information access, initial needs assessment, counseling process (chat or video call), evaluation, and follow-up. Feedback from peer evaluators indicates the service is easy to use, helpful, and flexible. The implication is that digital BK services can increase accessibility, student openness, and effectiveness of guidance services in schools.